TRADISI MASSAGALA PADA ETNIK TO BALO DI DESA BULO-BULO KECAMATAN PUJANANTING KABUPATEN BARRU - Asy'ary Ulama'i, Khaerul; Syamsuduhha Saleh; Indo Santalia; Mustamin Giling; Jusmiati (Rihlah : Jurnal Sejarah dan Kebudayaan, 2025)
This study aims to examine the Massagala tradition of the To Balo ethnic group in Bulo-Bulo Village, Pujananting District, Barru Regency, as a cultural heritage that is still preserved amidst the current of modernization. This tradition is believed to be a form of ritual to cure kasiwiang skin diseases as well as a means of uniting and maintaining social and spiritual harmony in the To Balo community. This study uses a descriptive qualitative method with a historical, anthropological, sociological, and religious approach. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that (1) the history of the existence of the To Balo ethnic group is based on the myth of violating taboos and the process of assimilation of Bugis-Makassar culture; (2) The Massagala tradition is carried out every three years with three main stages, namely Appamassi, Appagallang, and Apparibba; (3) This tradition contains strong Islamic teachings, including religious values ​​(monotheism and fasting), social values ​​(deliberation, mutual cooperation, silaturahmi), and aesthetic values ​​(Elong Sagala art). The implications of this study indicate the importance of preserving local traditions as a reflection of the integration of culture and religion in maintaining the social identity and local wisdom of the To Balo community. This study also contributes to the development of cultural studies and understanding of Islamic values ​​in the context of locality.   Penelitian ini bertujuan untuk mengkaji Tradisi Massagala pada Etnik To Balo di Desa Bulo-Bulo, Kecamatan Pujananting, Kabupaten Barru, sebagai warisan budaya yang masih lestari di tengah arus modernisasi. Tradisi ini diyakini sebagai bentuk ritual penyembuhan penyakit kulit jenis kasiwiang serta sarana pemersatu dan penjaga harmoni sosial dan spiritual masyarakat To Balo. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan historis, antropologis, sosiologis, dan religius. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa (1) sejarah keberadaan Etnik To Balo dilatarbelakangi oleh mitos pelanggaran pantangan dan proses asimilasi budaya Bugis-Makassar; (2) Tradisi Massagala dilaksanakan setiap tiga tahun dengan tiga tahapan utama yaitu Appamassi, Appagallang, dan Apparibba; (3) Tradisi ini mengandung nilai-nilai ajaran Islam yang kuat, termasuk nilai religi (tauhid dan puasa), nilai sosial (musyawarah, gotong royong, silaturahmi), serta nilai estetika (seni Elong Sagala). Implikasi dari penelitian ini menunjukkan pentingnya pelestarian tradisi lokal sebagai cerminan integrasi budaya dan agama dalam menjaga identitas sosial dan kearifan lokal masyarakat To Balo. Penelitian ini juga memberikan kontribusi terhadap pengembangan studi budaya dan pemahaman nilai-nilai Islam dalam konteks lokalitas.